1992
DOI: 10.1007/bf00161234
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials specific for motion onset

Abstract: Motion-onset visual evoked potentials were studied in 140 subjects by means of motion-onset stimulation either on a television screen or through back projecting via a moving mirror. The motion-onset visual evoked potentials were characterized in 94% of the population by a dominant negative peak with latency in the range of 135-180 ms. Motion-onset visual evoked potentials with a dominant positive peak, as described in the literature, seemed to be a variant of pattern-off visual evoked potentials, caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 11 publications
12
66
1
Order By: Relevance
“…Previous studies have shown that motion onset and oVset VEP are characterised by a negative peak, speciWc to motion that occurs just prior to 200 ms post stimulus onset (Spekreijse, Dagnelie, Maier, & Regan, 1985;Kuba & Kubová, 1992;Markwardt et al, 1988;Schellart et al, 2004). This negative peak evoked by the motion onset was barely manifest in the data from the detection task (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have shown that motion onset and oVset VEP are characterised by a negative peak, speciWc to motion that occurs just prior to 200 ms post stimulus onset (Spekreijse, Dagnelie, Maier, & Regan, 1985;Kuba & Kubová, 1992;Markwardt et al, 1988;Schellart et al, 2004). This negative peak evoked by the motion onset was barely manifest in the data from the detection task (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…and "Has it changed its speed and direction?" In the inspection condition, where no reaction was required, the motion onset VEP were characterised by the speciWc negative peak with its latencies ordered according to the velocity (cf., Kuba & Kubová, 1992;Markwardt et al, 1988). The structure of these latencies was very similar to that of the manual RT described by a negative exponential function with the power equal to ¡2/3.…”
Section: Discussionmentioning
confidence: 95%
“…Motion-onset VEPs have, however, properties that indicate that they might give information not obtainable from other types of VEPs. For example, motion-onset VEPs are recordable up to about 50 ~ of eccentricity [2], and their amplitudes are significantly larger to extramacular than to macular stimulation [2,3]. Thus, motion VEPs seem to be more suitable for testing peripheral parts of the retina (e.g., in patients with glaucoma) than any other type of VEP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, motion VEPs seem to be more suitable for testing peripheral parts of the retina (e.g., in patients with glaucoma) than any other type of VEP. It is also of interest for clinical use that motion-onset VEPs are independent of the size of the stimulus elements [2,4]. This enables testing even in patients with low visual acuity (e.g., in amblyopia).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological and psychophysical studies of human motion perception Kuba and Kubovä (1992) described a specific signal, a negative component, with a peak latency of 150-250 msec (depending on stimulus contrast), produced by the onset of movement of a checkerboard pattern. This response is clearly distinguishable from the well-known positive going'pattern-onset, pattern-offset and pattern-reversal responses, which almost certainly arise from the striate cortex.…”
Section: Parallel Processing Of Orientation and Direction Of Motionmentioning
confidence: 99%